The Role of Fibrin-Related Markers in Disseminated Intravascular Coagulation Due to Sepsis - Maimun Zulhaidah Arthamin (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Sepsis leads to local and systemic activation of different response systems, including coagulation and fibrinolysis. An overwhelming inflammatory response may lead to organ failure, and the coagulation and fibrinolysis involvement may lead to Disseminated Intravascular Coagulation (DIC). Special regard is given to the diagnosis of DIC by the use of scoring systems, which are, APACHE II, SAPS II, International Society of Thrombosis and Hemostasis (ISTH), and Japanese Ministry of Health and Welfare (JMHW). A large variety of fibrin compounds can be detected in plasma from septic patients with intravascular coagulation activation. Coagulation activation is indicated by elevated plasma levels of D-dimer, prothrombin fragments, and Thrombin-Antithrombin (TAT) complexes. Fibrin-Related Markers (FRMs) identified in sepsis are D-dimer, fibrinogen, Soluble Fibrin Monomer (SFM), and Fibrin Degradation Products (FDP). Hemostatic molecular markers, such as TAT, Plasmin-Plasmin Inhibitor Complex (PPIC), D-dimer, and SFM are better for the diagnosis of pre-DIC. No single biomarker of sepsis may be ideal, but many are helpful in terms of at least identifying critically ill patients who need more careful monitoring. As each biomarker has limited sensitivity and specificity, it may be interesting to combine several biomarkers. The purpose of this literature review was to increase knowledge about laboratory tests of FRMs and provide current knowledge and insight into these biomarkers related to DIC-sepsis. The method used in this literature review was a traditional review. Search, identify, and select relevant literature on PubMed–CBI and Google Scholar based on keywords, 30 journals were obtained from the two search engines.